Reporting the news : between commitment and constraints of journalistic practice - a study on broadcast journalists in the television network / Siti Zabedah Mohd Shariff - Mohd Shariff, Siti Zabedah (2009)
The study attempts to identify the level of commitment of local TV broadcast journalists in performing their job in news reporting in three different TV organizations - RTM1, a government-owned network; TV3, the first private television station and ntv7, the first digital television station in the country. This study also examines the level of journalistic autonomy among these news workers due to constraints they face in doing the job. Thus, the study leads to the understanding of the TV broadcast journalists' working environment in the different newsroom. Data are obtained from participation-observation done at the TV stations and in-depth interviews conducted with selected participants. The findings indicate that the TV broadcast journalists of the three stations have shown the desired characteristic of being journalists. There is also a strong positive correlation on job performance among them. It is found that commitment to the duty as journalists bind them to stay and to comply with the requirements of the workplace. However, they seek only to reveal and to convey to the audience news items that are influenced and shape by the supra-organization level. Organization rules, editorial policies and other influences as well as pressures forced them to adhere to these needs. Hierarchical organization control happens to override in RTM1 that resulted to shape the news more on government activities rather than reports on the public on actual incidents. Thus, a lesser degree of journalistic autonomy given to TV broadcast journalist in the station. In the case of TV3 and ntv7, journalistic autonomy among its their TV broadcast journalists still exist due to the trust given by editors in handling the news items they are assigned to. The news in TV3 and ntv7 is also shape by the imperialism of the business side of the media organization that is Media Prima Berhad. On job perception, the TV broadcast journalists have continuous positive attitude in doing their job as journalists in spite of the constraints they face. They are optimistic and do their work according to the journalistic practice.